2006
DOI: 10.1007/s10162-006-0028-9
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Measurement of Noise-Activated Middle-Ear Muscle Reflex and Stimulus Frequency Otoacoustic Emissions

Abstract: Otoacoustic emissions serve as a noninvasive probe of the medial olivocochlear (MOC) reflex. Stimulus frequency otoacoustic emissions (SFOAEs) elicited by a low-level probe tone may be the optimal type of emission for studying MOC effects because at low levels, the probe itself does not elicit the MOC reflex J. Assoc. Res. Otolaryngol. 4:521]. Based on anatomical considerations, the MOC reflex activated by ipsilateral acoustic stimulation (mediated by the crossed olivocochlear bundle) is predicted to be stron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 43 publications
(55 citation statements)
references
References 62 publications
3
52
0
Order By: Relevance
“…It was assumed that the 226 Hz probe tone is only sensitive to the acoustic impedance change of the middle ear induced by the MEM reflex because SFOAEs are extremely difficult to measure at this low-frequency range (Goodman and Keefe 2006). The choice of the 602-Hz probe tone was based on Feeney et al (2003) which showed that the greatest change in reflectance due to the MEM reflex was approximately around this frequency.…”
Section: Measuring Mem Reflexmentioning
confidence: 99%
See 3 more Smart Citations
“…It was assumed that the 226 Hz probe tone is only sensitive to the acoustic impedance change of the middle ear induced by the MEM reflex because SFOAEs are extremely difficult to measure at this low-frequency range (Goodman and Keefe 2006). The choice of the 602-Hz probe tone was based on Feeney et al (2003) which showed that the greatest change in reflectance due to the MEM reflex was approximately around this frequency.…”
Section: Measuring Mem Reflexmentioning
confidence: 99%
“…These results were consistently lower than those obtained with the commercial middle-ear analyzer (Interacoustics Audio Traveller AA220). Two previous papers have developed SFOAE-based techniques to measure the MEM reflex threshold Goodman and Keefe 2006). In both of these publications, the lowest elicitor level shown to evoke the MEM reflex was between 55 and 60 dB SPL.…”
Section: Influence Of Mem Reflexmentioning
confidence: 99%
See 2 more Smart Citations
“…Also, the sound transmission through the outer and middle ear was expected to be linear (Merchant et al, 1996) with the exception of the acoustic reflex that may have affected the transmission at the higher levels for the low-frequency sound (Neumann et al, 1996;Zhao et al, 2010). It has been shown that the acoustic reflex may be elicited at stimulation levels down to 50 to 60 dB SPL (Goodman et al, 2006;Zhao et al, 2010). Consequently, the acoustic reflex may influence the sound transmission for the low-frequency sound at levels above 50 dB SPL.…”
Section: Non-linear Sound Transmissionmentioning
confidence: 99%